Relationships Between Precipitation Properties and Large‐Scale Conditions During Subsidence at the Eastern North Atlantic Observatory. Issue 7 (7th April 2020) - Lamer, Katia; Naud, Catherine M.; Booth, James F.
Abstract: Three years of reanalysis and ground‐based observations collected at the Eastern North Atlantic (ENA) observatory are analyzed to document the properties of rain and boundary layer clouds and their relationship with the large‐scale environment during general subsidence conditions and following cold front passages. Clouds in the wake of cold fronts exhibit on average a 10% higher propensity to precipitate and higher rain‐to‐cloud fraction than cloud found in general subsidence conditions. Similarities in the seasonal cycle of rain and of large‐scale properties suggest that the large‐scale conditions created by the cold front passage are responsible for the unique properties of the rain forming in its wake. The identification of monotonic relationships between rain‐to‐cloud fraction and rain rate with surface forcing and boundary layer stability parameters as well as between virga base height with stability and humidity measures further supports that large‐scale conditions impact precipitation variability. That being said, these relationships between the large‐scale and rain properties are less clear than those established between cloud and rain properties, suggesting that cloud macrophysics have a more direct impact on the properties of rain than the large‐scale environment. The applicability of previously documented relationships between cloud thickness and rain properties is tested and the relationships adjusted to accommodate the complex shallow clouds and melting precipitation observed to occur in the ENA region. Establishing these relationships opens up opportunities for parametrization development and suggests that a realistic representation of precipitation properties in models relies on the accurate representation of both clouds and the large‐scale environment. Key Points: During periods of large‐scale subsidence in the Eastern North Atlantic, rain properties are strongly related to cloud thickness even in ice‐topped clouds Likely because of their relationship to cloud thickness, surface forcing and boundary layer stability impact rain fraction and rain rate Post‐cold frontal shallow clouds precipitate more frequently and have a higher rain‐to‐cloud fraction than clouds in general subsidence